2006
DOI: 10.1038/sj.ijo.0803383
|View full text |Cite
|
Sign up to set email alerts
|

The association between early childhood stunting and weight status in late adolescence

Abstract: Background: Cross-sectional studies have shown associations between stunting and overweight; however, there are few prospective studies of stunted children. Objectives: To determine whether stunting before age 2 years is associated with overweight and central adiposity at 17-18 years and whether growth in height among stunted children predicts body mass index (BMI) in late adolescence. Design: Prospective cohort study. Participants: One-hundred and three participants stunted by age 2 years and 64 non-stunted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 21 publications
3
38
2
4
Order By: Relevance
“…A greater prevalence of overweight in stunted children has been reported in cross-sectional studies (11, 12). These findings are not consistent with prospective studies that have found that stunting in early childhood is associated with decreased BMI or body fat in childhood (13, 14), adolescence (1517), and adulthood (18), and other prospective studies have found null associations (17, 19, 20). To our knowledge, few studies have measured outcomes at >1 follow-up age (13, 14, 17), and none have considered age-specific patterns of overweight incidence and reversion.…”
Section: Introductioncontrasting
confidence: 98%
“…A greater prevalence of overweight in stunted children has been reported in cross-sectional studies (11, 12). These findings are not consistent with prospective studies that have found that stunting in early childhood is associated with decreased BMI or body fat in childhood (13, 14), adolescence (1517), and adulthood (18), and other prospective studies have found null associations (17, 19, 20). To our knowledge, few studies have measured outcomes at >1 follow-up age (13, 14, 17), and none have considered age-specific patterns of overweight incidence and reversion.…”
Section: Introductioncontrasting
confidence: 98%
“…Indeed, results on early growth stunting and later visceral adiposity have been mixed. 37 An obesogenic environment may be the critical component in the association of early life catch-up growth with later obesity and/or increased VAT. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Stunted and short height-for-age individuals may be at an increased risk of overweight or obesity (OW/OB) during the growing years compared with their non-stunted peers (Bogin and Loucky 1997;Smith et al 2003;Martins et al 2004;Hoffman et al 2007;Walker et al 2007;Corvalan et al 2008;Mardones et al 2008). Changes in resting metabolic rate (RMR) occur during the first 5 years of life (Grillo et al 2005), the same period that stunting most often occurs (Fox and Hillsdon 2007).…”
Section: Introductionmentioning
confidence: 98%